Conservation publications and their provisions to protect research participants. Issue 1 (14th June 2019) - Ibbett, Harriet; Brittain, Stephanie
Abstract: Social science methods are increasingly applied in conservation research. However, the conservation sector has received criticism for inadequate ethical rigor when research involves people, particularly when investigating socially sensitive or illegal behaviors. We conducted a systematic review to investigate conservation journals' ethical policies when research involves human participants, and to assess the types of ethical safeguards documented in conservation articles. We restricted our review to articles that used social science methods to gather data from local people about a potentially sensitive behavior: hunting. Searches were conducted in the Web of Science, Scopus, and Google Scholar for research articles in English published from January 2000 to May 2018. Only studies conducted in countries in south and Southeast Asia, Africa, and Central and South America were considered. In total, 4456 titles and 626 abstracts were scanned, with 185 studies published in 57 journals accepted for full review. For each article, any information regarding ethical safeguards implemented to protect human participants was extracted. We identified an upward trend in the documentation of provisions to protect human participants. Overall, 55% of articles documented at least one ethical safeguard. However, often safeguards were poorly described. In total, 37% of journals provided ethics guidelines and required authors to report ethical safeguards in manuscripts, but a significant mismatch between journal policies and publication practice was identified. Nearly, half the articles published in journals that should have included ethics information did not. We encourage authors to rigorously report ethical safeguards in publications and urge journal editors to make ethics statements mandatory, to provide explicit guidelines to authors that outline journal ethical reporting standards, and to ensure compliance throughout the peer‐review process. Abstract : Publicaciones sobre Conservación y sus Aportaciones para Proteger a los Participantes de la Investigación Resumen: La metodología de las ciencias sociales cada vez se aplica más en la investigación para la conservación. Sin embargo, el sector de la conservación ha recibido críticas por un rigor ético inadecuado cuando la investigación involucra a las personas, particularmente cuando se investigan comportamientos ilegales o socialmente sensibles. Realizamos una revisión sistemática para investigar las políticas éticas de las revistas de conservación cuando la investigación involucra a participantes humanos y para evaluar los tipos de salvaguardas éticos documentados en los artículos de conservación. Restringimos nuestra revisión a artículos que usaron metodología social para recolectar datos de la gente local sobre un comportamiento potencialmente sensible: la cacería. Las búsquedas se realizaron en los sitios Web of Science, Scopus y Google Scholar enfocadas en los artículos de investigación en inglés publicados entre enero del 2000 y hasta mayo del 2018. Solamente consideramos los estudios realizados en los países del sur y sureste de Asia, África y Centro y Sudamérica. Un total de 4456 títulos y 626 resúmenes fueron escaneados. Revisamos completamente 185 estudios publicados en 57 revistas aceptadas. Se extrajo cualquier información con respecto a los seguros éticos implementados para proteger a los participantes humanos. En general, el 55% de los artículos documentaron al menos un seguro ético. Sin embargo, con frecuencia los seguros eran descritos pobremente. En total, el 37% de las revistas proporcionaron guías éticas y requirieron que los autores reportaran los seguros éticos en los manuscritos, pero se identificó una discrepancia significativa entre las políticas de las revistas y las prácticas de publicación. Casi la mitad de los artículos publicados en las revistas que deberían haber incluido información ética no la tuvo. Alentamos a los autores a que reporten con rigurosidad los seguros éticos en las publicaciones y les urgimos a los editores de dichas revistas que hagan obligatorias las declaraciones éticas, que proporcionen a los autores guías explícitas que resuman los estándares de reportaje ético de las revistas en línea, y que aseguren el cumplimiento por medio del proceso de revisión por pares. Abstract : Article impact statement : Conservation articles often poorly describe ethical safeguards, and journals should ensure authors report ethical considerations.